Communicated Accountability Of Charitable Organisations: The Case Of Nigeria - Musawa, Mubarak Shehu (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2019)
The aim of this study is to examine how accountability is practised by charity institutions in Nigeria.The paper employs Ebrahim"™s charity accountability framework to analyse BudgIT"™s website, public related documents and news. It is observed that the practice of accountability by BudgIT lays emphasis on upward accountability to donors, focused on primarily reporting basic descriptive financial and performance information. However the research is based on a content analysis of a single charity organisation and, therefore, any generalising of the conclusions beyond BudgIT may not represent the reporting behaviour of all charity institutions in Nigeria.This paper is among the few studies that investigate the reporting behaviour of charitable institutions in a developing country, thus contributing to the scanty literature on charitable accountability in Nigeria.